Investigation of the synergistic effect of porphyrin photosensitizer on graphene–TiO2 nanocomposite for visible light photoactivity improvement. Issue 3 (17th November 2015) - Rahimi, Rahmatollah; Zargari, Solmaz; Ghaffarinejad, Ali; Morsali, Ali
Abstract : To use the visible light in photodegradation reactions efficiently, graphene–TiO2 nanocomposite was photosensitized using tetrakis(4‐carboxyphenyl)porphyrin. To investigate the effect of graphene as well as dye sensitization on the photoactivity of the synthesized photocatalyst, photocatalytic properties and photocurrent responses of the prepared samples were examined under visible light irradiation. A twofold increase of photocurrent response in the TG nanocomposite photosensitized with porphyrin (TGP) compared to TG (3%) nanocomposite provides an evidence of the effective influence of the porphyrin photosensitizer in the visible light photoactivity enhancement. There is a complete correspondence between the photocatalytic activity and photocurrent response of the photocatalysts. The photocatalytic properties of the photocatalysts were carried out in the degradation of methyl orange and bisphenol A under visible light irradiation. It was determined that TGP compound was stable after photocatalytic process and degraded 93% of methyl orange and 85% of bisphenol A in 240 min under visible light irradiation. Furthermore, the mechanism of investigation of the photocatalytic process determines that O 2 .− and OH . are the main reactive species for degradation of methyl orange and bisphenol A over the TGP compound under visible light irradiation. © 2015 American Institute of Chemical Engineers Environ Prog, 35: 642–652, 2016